Twitter Sentiment Analysis on The use of Sinovac Vaccine in Indonesia - Sherly Trisnawati; Akhmad Unggul Priantoro; Chairani Fauzi; Riko Herwanto; Hari Sabita (Proceeding International Conference on Information Technology and Business, 2021)
Coronavirus Diseases (Covid-19) was reported the first time in Wuhan, Hubeu Province, China 2019. On March 11 th 2021 World Health Organization (WHO) declared covid-19 as a world pandemic. To reduce the number of deathsand the number of the transmission of covid-19 is by the vaccination. Several vaccines have been evaluated by WHO to against covid-19, Indonesian Government officially announced the use of Sinovac Vaccine produced by Sinovac Life ScienceCo, China. This vaccination topic becomes one of the massive topics discussed by the Indonesian people and various responses on social media such as Twitter. The technique used, is crawling tweets from Twitter users worldwide using theEnglish language from May 24 th 2021 – August 31 2021 with the keyword “sinovac vaccine”. This study aims to analyze public sentiment regarding the usage of sinovac vaccine in Indonesia. The method used is Naïve Bayes because it has a simple algorithm with high accuracy. The result shows the classification accuracy rate is 80.99% and majorities’ responds are neutral and positive. However, the preprocessing data has the rule to get excellent result for the accuracy. Future studycan also classify the tweets into different queries and other classification methods can be applied such as Super Vector Machine and KNN. Keywords— Covid-19, Sinovac Vaccine, Sentiment Analysis, Naïve Bayes